Utrophin upregulation in Duchenne muscular dystrophy. - Hirst, R; McCullagh, K; Davies, K (2005)
Duchenne Muscular Dystrophy (DMD) is a devastating, progressive muscle wasting disease for which there is currently no effective treatment. DMD is caused by mutations in the dystrophin gene many of which result in the absence of the large cytoskeletal protein dystrophin at the sarcolemma. Over-expression of utrophin, the autosomal paralogue of dystrophin, as a transgene in the mdx mouse (the mouse model of DMD) has demonstrated that utrophin can prevent the muscle pathology. Thus, up-regulation of utrophin in DMD muscle is a potential therapy for DMD. In this review we discuss recent advances in our understanding of the regulatory pathways controlling utrophin expression and the various approaches that have been applied to increasing the level of utrophin in the mdx mouse. These results are very encouraging and suggest that pharmacological up-regulation of utrophin may well be a feasible approach to therapy for DMD.